2017
DOI: 10.20319/pijss.2017.32.21222134
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Assessment in the Context of Secondary School Physical Education Teachers in Malaysia

Abstract: The purpose of this study is to explore the implementation of School-Based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Lebar et al (2013) noted that PHE teachers lack proficiency in constructing test items and clarity regarding what constitutes effective assessments. Similarly, Veloo and Krishnasamy (2017) reported that teachers did not have a clear understanding of PHE assessment requirements, with this lack of understanding being particularly prevalent among non-option teachers. Abdullah et al (2015) revealed that only 30 percent of the PHE teachers in their study had the competency to develop assessment instruments.…”
Section: Physical and Health Education (Phe) Teachers' Assessment Pra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lebar et al (2013) noted that PHE teachers lack proficiency in constructing test items and clarity regarding what constitutes effective assessments. Similarly, Veloo and Krishnasamy (2017) reported that teachers did not have a clear understanding of PHE assessment requirements, with this lack of understanding being particularly prevalent among non-option teachers. Abdullah et al (2015) revealed that only 30 percent of the PHE teachers in their study had the competency to develop assessment instruments.…”
Section: Physical and Health Education (Phe) Teachers' Assessment Pra...mentioning
confidence: 99%
“…The validity and reliability of assessment practices are critical, ensuring that evaluations provide meaningful insights into students' abilities and areas for growth (Parsak & Sarac, 2021;Veloo, 2016;Veloo & Ali, 2016). The literature measuring PHE teachers' assessment practices suggests that teachers' adeptness in assessment activities directly influences the quality of instruction Sitovskyi et al (2019); Van Munster et al (2019); Veloo & Krishnasamy (2017); student engagement Arefiev et al (2020); Parsak & Sarac (2021); Rafi & Pourdana (2023); and overall learning outcomes in PHE (Mohamed et al, 2019;Rongchan, 2020;Wee, 2019;Wee et al, 2021). Effective assessment strategies not only inform teachers about students' progress but also guide instructional decisions, allowing for tailored interventions to address individual learning needs (Arefiev et al, 2020;Colquitt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies measuring Malaysian PHE teachers' issues and challenges in CBA implementation often involved examining the aspect from instructional perspectives (Zakaria et al, 2024). Sports equipment and facilities (Mohamed et al, 2019;Veloo & Ali, 2016;Veloo & Krishnasamy, 2017;Wee, 2019;Wee et al, 2020); teachers' content knowledge Veloo & Ali (2016); Veloo & Krishnasamy (2017) and pedagogical content knowledge (PCK) Veloo & Ali (2016); Wee et al (2020); student and parent factors Kilue & Mohamad (2017) were salient themes in literature on issues and challenges to effective PE implementation. Administrators' attitudes and perceived lack of support were also strongly acknowledged.…”
Section: Malaysian Physical and Health Education Teachers' Assessment...mentioning
confidence: 99%
“…Administrators' attitudes and perceived lack of support were also strongly acknowledged. School administrators were found to weight and prioritize core subjects, particularly subjects included in the Sijil Pelajaran Malaysia (SPM), over PHE Fonyi & Soon (2021); Wee (2017); less responsive in resolving issues pertaining to PHE teaching and learning improvements Veloo & Krishnasamy (2017); Wee et al (2020); and were more likely to assigned untrained teachers to teach PHE to complete the teachers' weekly loading hours (Wee & Chin, 2020).…”
Section: Malaysian Physical and Health Education Teachers' Assessment...mentioning
confidence: 99%